Religious and cultural influences: An exposition - Gideon Imoke Emeng; Justin Oyebuchi Okafor (Center for Humanities and Innovation Studies, 2022)
Religion and culture seem to be complicated concepts from an international relations viewpoint. Scholars and philosophers have, after all, long discussed the meaning of these words and their influence on our understanding of the social world. The purpose of this paper is to provide a diagram of religion and culture in international politics. The purpose was to highlight the significance of religious and cultural influences in understanding world events. The process consisted of identifying the characteristics of each concept and analyzing their impact on personal, national, and international experiences. This work argues that understanding religious and cultural issues is necessary to engage in some of the most important discussions about current world affairs. This work submits that there is nothing in modern IR that does not include religion, culture, or both. This research is carried out using critical and contextual analysis methods.